EVALUATING FACTORS INFLUENCING ASPHALT ROAD CONSTRUCTION QUALITY IN HIGH TEMPERATURE CONDITION (CASE STUDY) - El atrash, Khlifa Saad; Assaf , Gabriel J. (Journal of Civil Engineering, Science and Technology, 2019)
The assumption of a linear viscoelastic behaviour of asphalt mixes suggests that the response of the material to the inquiry, is the sum of the responses of that material to each elementary petition. However, the construction of asphalt concrete pavements (CAP) is a complicated procedure, including some of climate parameters and material availability. Hot weather environment, such as Libya, has its own challenges and requirements in terms of weather factors, materials, construc-tion equipment, and the availability of materials in each area. However, the condition of some roads seems to be below the required level. Rutting distress is one of the major defects that occur in asphalt pavements in the hot region weather of Libya and has severely influenced drive-ability. Questionnaires and laboratory experiments were conducted for several mixtures at representative temperature and traffic load. In this study, rutting tests were conducted on two different mixtures. The first blind used traditional asphalt bitumen type B (60/70), while another blind was carried out using the Superpave design procedure using asphalt bitumen type performance grade PG (70-10). The questionnaire was sent to tens of engineers and specialists. The interview was carried out with a few others, in which the interview was among the factors that explained the unsatisfactory performance of the asphalt roads in Libya. The results showed that the consideration and improvement of these factors play an important role in improving the characteristics of the road surface, increasing service life, and reducing maintenance costs. ACP should employ asphalt bitumen, which works perfectly in the Libyan environment. Materials properties in asphalt mixture displayed high impact of the pavement performance.